Drugs, insecurity and failed states: the problems of prohibition - Inkster, Nigel (Adelphi series, 2012)
The world's wealthiest nations have expended vast blood and treasure in tracking and capturing traffickers, dealers and consumers of narcotics, as well as destroying crops and confiscating shipments. Yet the global trade in illicit drugs is thriving with no apparent change in the level of consumption despite decades of prohibition. This Adelphi argues that the present enforcement regime is not only failing to win the "war on drugs"; it is also igniting and prolonging that conflict on the streets of producer and transit countries, where the supply chain has become interwoven with state institutions and cartels have become embroiled in violence against their rivals and with security forces. What can be done to secure the worst affected regions and states, such as Latin America and Afghanistan? By examining the destabilizing effects of prohibition, as well as alternative approaches such as that adopted by the authorities in Portugal, this book shows how progress may be made by treating consumption as a health-care issue rather than a criminal matter, thereby freeing states to tackle the cartels and traffickers who hold their communities to ransom